Does asymptomatic recurrent diffuse capillary C4d complement deposition impair cardiac allograft function?. Issue 10 (24th September 2016) - Frea, Simone; Iacovino, Cristina; Botta, Michela; De Filippi, Ilaria; Mazzucco, Gianna; Pidello, Stefano; Biolè, CarloAlberto; Bergerone, Serena; Boffini, Massimo; Praticò Barbato, Loredana; Morello, Mara; Rinaldi, Mauro; et al.
Abstract: Background: The aim of this study was to evaluate whether asymptomatic recurrent (≥2) antibody‐mediated rejection (pAMR 1+), defined as diffuse capillary C4d immunostaining (rAMR) on endomyocardial biopsies (EMBs), during the first year after heart transplantation impairs left ventricular (LV) function. Methods: Fifty‐four consecutive heart transplant patients who survived well (New York Heart Association ≤2 and EF≥55%) the first month after transplantation were enrolled and prospectively underwent 490 echocardiographies and EMB. Asymptomatic rAMR without histopathologic findings was evaluated as a risk factor for deterioration of graft function. Primary endpoint, assessed 1 year after transplantation, was development of LV dysfunction and/or adverse remodeling according to pre‐specified echo parameters. Results: During the first year from transplantation, rAMR occurred in five patients. Recurrent AMR was associated with a significant higher risk to develop LV concentric hypertrophy (OR 3.6, 95% CI: 1.8–7.0, P =.02) or reduced lateral S′ peak velocity (OR 2.3, 95% CI: 1.5–3.6, P =.03). Patients with rAMR showed significative adverse graft remodeling (ΔLV end‐diastolic volume: +16±12.3 vs −0.2±14.4 mL; P =.02) and deterioration of graft function (Δlateral S′ peak velocity: −3.3±3 vs −0.4±2.9 cm/s; P =.03). Conclusions: Recurrent asymptomatic diffuse capillary C4d immunostaining may play a role in the early development of cardiac allograft adverse remodeling and dysfunction.